Clinical efficacy analysis of anterior superior iliac spine 3D-printed guide plate-assisted sacroiliac screw placement for the treatment of pelvic fractures - Chen, Lin; Luo, Lan; Zhang, Xulin; Li, Lei; Liu, Dong (Frontiers in Surgery, 2025)
ObjectiveThe aim of this study was to compare the clinical outcomes of percutaneous 3D-printed guides in the anterior superior iliac spine site with traditional fluoroscopy-assisted sacroiliac screw implantation for the treatment of pelvic fractures.MethodsIn total, 40 patients with eligible pelvic fractures who were diagnosed and treated between December 2022 and May 2024 were enrolled and divided into two groups. The guide plate group used anterior superior iliac spine 3D-printed guide plate-assisted sacroiliac screws to fix the posterior pelvic ring fracture; the fluoroscopy group used fluoroscopic freehand placement of sacroiliac screws to fix the posterior pelvic ring fracture. The operative time, number of fluoroscopies, amount of intraoperative bleeding, and length of incision for each screw implantation in the two groups were recorded. Fracture reduction was evaluated according to Matta’s criteria, screw position was assessed using modified Gras classification, and a statistical analysis was performed.ResultsAmong the 40 patients who were followed up for 6–12 months, 23 sacroiliac screws were implanted in 20 patients in the guide plate group and 25 sacroiliac screws were implanted in 20 patients in the fluoroscopy group. The operative times were 50–75 (60.00 ± 8.429) min and 50–90 (72.25 ± 10.939) min (P < 0.001) in the guide plate group and fluoroscopy group, respectively, while the number of fluoroscopies was 7–18 (11.65 ± 3.117) and 38–62 (48.05 ± 7.258), respectively (P < 0.001), and the amount of intraoperative bleeding was 10–30 (16.60 ± 5.642) mL and 5–20 (10.3 ± 4.354) mL, respectively (P < 0.001). Matta’s criteria scores for fracture repositioning in the two groups were excellent and good, respectively (P = 0.429). Modified Gras classification was used to assess the screw positions, with 19 in class I, 4 in class II, and 0 in class III in the guide plate group and 20 in class I, 4 in class II, and 1 in class III in the fluoroscopy group. The difference between the two groups was not statistically significant (P = 0.624).ConclusionAnterior superior iliac spine 3D-printed guide plate-assisted sacroiliac screw fixation of pelvic fracture, when compared with traditional fluoroscopy-assisted sacroiliac screw fixation of pelvic fracture, has a shorter operation time, reduces the number of fluoroscopies, and improves the accuracy of implantation.